Relationship Between Knowledge And Family Support Towards Anemia Prevention Behavior In Pregnant Women At Genteng Kulon Community Health Center - Febrika Devi Nanda; Hendrik Probo Sasongko (International Journal of Health and Medicine, 2025)
Pregnancy is the growth and development of an intrauterine fetus starting from conception and ending until the start of labor. The duration of pregnancy from ovulation to parturition is approximately 280 days (40 weeks). One of the problems that often occurs is anemia in pregnancy. Many pregnant women do not know about anemia and how to prevent it. The factors that influence the level of maternal knowledge about preventing anemia are education, age, type of work, gestational age. The purpose of this study was to determine the level of knowledge and support of families towards pregnant women. This study used a quantitative descriptive design with a Spearman rho statistical test research design and used the technique snowball sampling. The instrument in this study was a questionnaire about the level of knowledge of pregnant women, family support and preventive behavior. The location was at the Genteng Kulon Health Center, Genteng District in July 2024. From the results of the study with the Spearman rho statistical test using SPSS on the level of knowledge, it was found that the level of significance value of 0.001. At the Genteng Kulon Health Center, Genteng District. From the results of this study, it is suggested that there is a need for direction and counseling from officers for IEC to pregnant women regarding increasing pregnant women and family support for anemia prevention behavior in pregnant women.